Traditions Of Jews Living In Kutaisi: (Culinary, Marriage, Clothing Habits) - Khatchapuridze, Ramaz (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2018)
The basis of spirituality, nationality was a family, which used to live separately but shared the joy and trouble of each-other. These kinds of families retained the best national traditions, developed the national culture. If we have something good today, remained from the past, it the exploits of families. These families, of course, were intelligent families but of course there were some, who made living with trading. Jew neighbors were the assets of Kutaisi residents. In terms of the formation of this nature, the significant role had monotheist religion - Judaism. Jes used to live in different countries and were involved in common economic, societal-political, and cultural lives of each population. In 1948 with the decision of the UN General Assembly Jewish state Israel was born with the official language Ivrit, which means the Jewish language. According to the results of the population record held in 2002, 4 000 Jews live in Georgia. Their majority lives in Tbilisi, Kutaisi, Batumi, Rustavi, Akhaltsikhe, as for villages they were almost neglected by Jews. Synagogues are acting in Tbilisi, Kutaisi, Batumi, Gori, Oni, Akhaltsikhe and Surami. The cultural traditions of “ethnic neighbors” are very interesting, Jewish cuisine rules, their wedding traditions, etc.